Use of antipsychotic medication and its relationship with bone mineral density: A population-based study of men and women - Azimi Manavi, Behnaz; Stuart, Amanda L.; Pasco, Julie A.; Hodge, Jason M.; Samarasinghe, Rasika M.; Weerasinghe, D. Kavindi; Williams, Lana J. (Frontiers in Psychiatry, 2023)
Abstract Backgrounds: Schizophrenia has been shown to be associated with reduced bone mineral density (BMD)and higher fracture risk. However, less is known whether antipsychotic treatment is associated with reduced BMD. We hypothesis that there is a significant association between antipsychotic use and BMD. Thus, we aimed to examine associations between antipsychotic use and BMD among men and women drawn from the general population. Methods: This cross-sectional study involved 793 women and 587 men enrolled in the Geelong Osteoporosis Study. BMD was determined using dual energy x-ray absorptiometry at the spine and hip. Information regarding socio-economic status (SES), current medication and/or supplementation use, lifestyle factors and anthropometry was collected. Association between antipsychotic use and BMD was determined using linear regression after adjusting for potential confounders. Results: Of the group, 33 women (4.2%) and 16 men (2.7%) currently used antipsychotics. Age was identified as an effect modifier in the association between antipsychotic use and BMD for women. Amongst women aged <60 years, adjusted mean BMD was 11.1% lower at the spine [1.139 (95%CI 1.063-1.216) vs. 1.250 (95%CI 1.223-1.277) g/cm2, p=0.005] for antipsychotic users compared to non-users. At the hip, age, weight and smoking adjusted mean BMD was 9.9% lower [0.893 (95%CI 0.837-0.950) vs. 0.992 (95%CI 0.976-1.007) g/cm2, p<0.001] for antipsychotic users in comparison with non-users. The pattern persisted following further adjustments. There was no association detected between antipsychotic use and BMD for women aged 60 years and over and for men. Conclusions: Our data suggest that antipsychotic medication use is associated with reduced BMD in younger women but not older women or men.